SUSTAINABLE RESOURCE EFFICIENCY AND CIRCULAR ECONOMY IN GLOBAL TEXTILE INDUSTRY (Global Conference on Multidisciplinary Research and Innovation, 2026)
This study examines sustainable resource efficiency and circular economy practices in the global textile industry. The study focuses on reducing material waste, optimizing water and energy consumption, and implementing recycling-based production systems. In recent years, environmental sustainability has become a key priority for textile manufacturers due to increasing regulatory pressure and rising production costs. The research is based on international reports and academic studies from organizations such as the European Environment Agency, Ellen MacArthur Foundation, and World Economic Forum. The findings indicate that sustainable production models significantly improve both environmental and economic performance.
Keywords: Sustainability, textile industry, circular economy, resource efficiency, green manufacturing, waste reduction, energy optimization, environmental management